PATH FROM BEING AN ASSISTANT TO HEAD COACH - Erdem, Can (Sport- és Egészségtudományi füzetek, 2025)
In his motivational speech, Erdem Can shared his personal journey from assistant coach to head coach. The path was anything but straight; it was more like a rollercoaster. I began my career as a basketball player. All I knew was that I wanted to be the best basketball player in the world. But I got hurt when I was 17. At the age of 19, at my university professor’s advice I began coaching children aged 10 to 18 in all categories. I realized that there was another way to love basketball. The game has embedded itself in my body and soul. This is how my lifelong commitment to basketball began. I didn’t speak English at the time, but I recognized the value of knowing the common language of basketball, so I studied it diligently. I attended a basketball camp in the United States where I learned that the only way to improve yourself is to invest in yourself.